Hubungan Gaya Hidup Terhadap Peningkatan Kualitas Hidup Pasien Hemodialisis Di Rumah Sakit Murni Teguh Sudirman Jakarta - Jolinda, Christine; Wahyu, Afnijar (Indonesian Trust Nursing Journal, 2025)
factors can cause chronic kidney failure (CKD), including lifestyle. CKD patients require hemodialysis due to endocrine, metabolic, electrolyte fluid and acid-base disorders as a substitute for kidney function to remove metabolic waste that will impact the patient's quality of life. The purpose of this study was to determine the relationship between lifestyle and improving the quality of life of patients at Murni Teguh Sudirman Hospital, Jakarta. This research method is a quantitative correlation study with a Cross Sectional design. The sample in this study was 30 chronic kidney failure patients who had undergone hemodialysis with a Consecutive sampling technique. The instrument used was a KDQOL-SF questionnaire. Bivariate data analysis used the chi-square test. The results obtained a p value = 0.009 where the p value is smaller than the critical limit value of 0.05 (p < α), which means there is a significant relationship between lifestyle and quality of life in hemodialysis patients. It can be concluded that the lifestyle of hemodialysis patients is related to improving their quality of life.